2000
DOI: 10.1007/s004210000234
|View full text |Cite
|
Sign up to set email alerts
|

Lipid and lipoprotein profiles, cardiovascular fitness, body composition, and diet during and after resistance, aerobic and combination training in young women

Abstract: The purpose of this study was to evaluate the effects of various modes of training on the time-course of changes in lipoprotein-lipid profiles in the blood, cardiovascular fitness, and body composition after 16 weeks of training and 6 weeks of detraining in young women. A group of 48 sedentary but healthy women [mean age 20.4 (SD 1) years] were matched and randomly placed into a control group (CG, n = 12), an aerobic training group (ATG, n = 12), a resistance training group (RTG, n = 12), or a cross-training g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
75
5
20

Year Published

2003
2003
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(118 citation statements)
references
References 25 publications
16
75
5
20
Order By: Relevance
“…Statistically significant changes were not found for any of the variables in the biochemical profile as in body composition, which is in contrast with LeMura et al 24 since in their study with sedentary young women showed that the aerobic group decreased TRI and increased HDL. Likewise Ghahramanloo et al 25 observed that sedentary young males showed significant improvements in HDL and LDL in the aerobic group and concurrent training.…”
Section: Discussioncontrasting
confidence: 90%
“…Statistically significant changes were not found for any of the variables in the biochemical profile as in body composition, which is in contrast with LeMura et al 24 since in their study with sedentary young women showed that the aerobic group decreased TRI and increased HDL. Likewise Ghahramanloo et al 25 observed that sedentary young males showed significant improvements in HDL and LDL in the aerobic group and concurrent training.…”
Section: Discussioncontrasting
confidence: 90%
“…These results are consistent with the results of some previous studies (21,22) and they are not in line with the results of some other studies (13)(14)(15). Some researchers have stated that enhancement of blood TG in response to exercise with a moderate intensity can be considered as a natural pattern of responding to blood lipids during puberty (13).…”
Section: Discussionsupporting
confidence: 81%
“…Coutts and others (2004) [3] observed that 12 weeks of direct supervision of resistance training in young athletes results in greater training adherence and increased muscular strength, power, and running speed. Similarly, LeMura and others (2002) [4] observed 16 weeks of various modes of resistance training and found significant improvement in upper and lower body strength. Dorgo and others (2009) [5] found significant improvements in muscular strength and muscular endurance of the manual resistance training and weight resistance training groups.…”
Section: Discussionmentioning
confidence: 73%